Radiative corrections and Spinney correlation with electromagnetic form factors of neutrino mass scattering on polarized electrons - Jabour , Jabour; Milhim, Jehad; Housin, Khaoulla (Latakia University Journal -Basic Sciences Series, 2018)
In this research, the differential cross-sections of the elastic scattering of neutrinos (anti neutrinos) In all its flavors off the polarized electron according to the experimental reality was calculated. It was found the radiative corrections in the differential cross-sections of the previous interaction arising from the inclusion of electromagnetic form factors of neutrino in the amplitude of interaction through the loop . The effect of helicity of neutrinos (antineutrinos) on the radiative corrections was studied. The spinney correlation in the case of polarization of both input and output electrons for three cases: Parallel state, inversion state, orthogonal state also studied. The degree of polarization of the target electron in the above three cases was calculated. The effect of electromagnetic form factors of neutrino that found in the expression of radiative corrections in deviation from the standard model was studied. The change in the degree of polarization of the output electron with its kinetic energy in the above three cases for all flavor of neutrinos to determine the relation between the polarization of output electron and the flavor of neutrino also studied.